An In Situ Cross‐Linked Nonaqueous Polymer Electrolyte for Zinc‐Metal Polymer Batteries and Hybrid Supercapacitors. Issue 35 (30th July 2020) - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, Manohar V.; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar
Abstract: This work reports the facile synthesis of nonaqueous zinc‐ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)‐light‐induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10 −3 S cm −1 . The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn 2+ and dendrite‐free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV‐polymerization‐assisted in situ process is developed to produce ZIP (abbreviated i‐ZIP), which is adopted for the first time to fabricate a nonaqueous zinc‐metal polymer battery (ZMPB; VOPO4 |i‐ZIP|Zn) and zinc‐metal hybrid polymer supercapacitor (ZMPS; activated carbon|i‐ZIP|Zn) cells. The VOPO4 cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of ≈1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc‐based energy storage technologies. Abstract : A nonaqueous zinc‐ion conducting polymer electrolyte (ZIP) with high oxidation stability of >2.4 V versus Zn|Zn 2+ is prepared by ultraviolet‐light‐assisted free‐radical polymerization. The ZIP is used in the fabrication of rechargeable zinc‐metal battery and hybrid supercapacitor by the in situ process, which involve the direct generation of polymer electrolyte over the electrode surface ensuring enhanced electrode|electrolyte interface.